2019
DOI: 10.1098/rsif.2018.0955
|View full text |Cite
|
Sign up to set email alerts
|

PEEK surface modification by fast ambient-temperature sulfonation for bone implant applications

Abstract: We develop a simple, fast and economical surface treatment under ambient temperature to improve the hydrophilicity and osteoconductivity of polyetheretherketone (PEEK) for bone implant applications. A major challenge in bone implants is the drastic difference in stiffness between traditional implant materials (such as titanium and stainless steel) and human bone. PEEK is biocompatible with an elastic modulus closely matching that of human bone, making it a highly attractive alternative. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
89
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 40 publications
10
89
2
Order By: Relevance
“…22 Subsequently, Li et al 23 reported that PEEK was sulfonated for 1 min and formed a 3 D porous network structure with a pore size of 0.5-2 mm, and Cheng et al 24 reported that after 3 min of sulfonation with 98% H 2 SO 4 , the SPEEK sample showed an optimized surface microporous network. The study discussing the optimal sulfonation time was released in 2019 by Wang et al, 25 in which sulfonation treatments under varying reaction times (5-90 s) were investigated and the hydrophilicity and morphology of SPEEK surfaces were evaluated. They considered that the 30 s sulfonation was optimal with consideration of both hydrophilicity and morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Subsequently, Li et al 23 reported that PEEK was sulfonated for 1 min and formed a 3 D porous network structure with a pore size of 0.5-2 mm, and Cheng et al 24 reported that after 3 min of sulfonation with 98% H 2 SO 4 , the SPEEK sample showed an optimized surface microporous network. The study discussing the optimal sulfonation time was released in 2019 by Wang et al, 25 in which sulfonation treatments under varying reaction times (5-90 s) were investigated and the hydrophilicity and morphology of SPEEK surfaces were evaluated. They considered that the 30 s sulfonation was optimal with consideration of both hydrophilicity and morphology.…”
Section: Introductionmentioning
confidence: 99%
“…27 In addition, the residual sulfuric acid was also wiped off using an NaOH solution by neutralization-reaction. 25 Even so, the optimal post-treatment methods after sulfonation of PEEK to remove residual sulfuric acid remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, appropriate physico-chemical modification of the PEEK surface, and its micro- and nanostructuring, can improve its bioactivity. Many techniques were used for PEEK modification, including chemical surface treatment [ 11 , 12 ], laser processing [ 13 , 14 ], and the most popular, which seems also to be the most universal—surface plasma treatment [ 15 , 16 ]. The effect of the exposure to plasma induces a variety of changes on polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk properties will influence device strength and stability, while the device surface interfaces directly with the body and influences cell attachment and biological response properties. Therefore, the direct chemical derivation of PEEK's surface to introduce cell binding groups can impart the desired biological response utilizing currently available PEEK manufacturing technology without impacting material mechanical or physical properties (other than hydrophilic and surface charge) (Poulsson et al 2019;Wang et al 2019). Changing PEEK's properties through direct surface modification is a new approach to creating next-generation materials with inherently improved cell growth properties (Kassick et al 2018).…”
mentioning
confidence: 99%
“…These approaches are the introduction of sulfonic acid moieties onto the aryl ring via etching with concentrated sulfuric acid. (Wang et al 2019;Shibuya and Porter 1992;Chaijareenont et al 2018) The introduction of the anionic surface charge promotes protein binding and deposition, creating an environment conducive to cell growth. In vivo evidence has emerged demonstrating the superiority of sulfonic acid-modified PEEK compared to native PEEK for support of bone ongrowth.…”
mentioning
confidence: 99%